2007
DOI: 10.1590/s1517-83822007000300016
|View full text |Cite
|
Sign up to set email alerts
|

Interference of tuberculosis on the performance of ELISAs used in the diagnosis of paratuberculosis in cattle

Abstract: Forty-four cows from five herds infected with tuberculosis (TB) and without paratuberculosis (PTB), and 21 cows from a herd without either infection were studied. The cattle presented concordant results in both the skin test and γ-interferon assay for TB and two commercial ELISAs for PTB. Animals were divided according to TB test results into Group A with 28 TB-infected animals, Group B with 16 TB-negative animals from infected herds, and Group C with 21 TB-negative cows from a tuberculosis-free herd (which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
(18 reference statements)
0
11
1
Order By: Relevance
“…Yet, when the individual results from the SIT or IGRA were analysed, a lack of association with JD positivity was observed, in contrast with previous studies 13 15 40 50 54. This could indicate that JD reactors were therefore not infected with M bovis , and therefore positivity in the JD-ELISA would not be due to cross-reactivity in M bovis- infected animals.…”
Section: Discussioncontrasting
confidence: 66%
“…Yet, when the individual results from the SIT or IGRA were analysed, a lack of association with JD positivity was observed, in contrast with previous studies 13 15 40 50 54. This could indicate that JD reactors were therefore not infected with M bovis , and therefore positivity in the JD-ELISA would not be due to cross-reactivity in M bovis- infected animals.…”
Section: Discussioncontrasting
confidence: 66%
“…The Johnin skin test for paratuberculosis, which is interpreted as positive when skin thickness increased ≥4 mm, is a specific and low-cost test for the early diagnosis of paratuberculosis in the majority of dairy herds, although the specificity of both tests is influenced by batch of PPD antigen and varies among herds (Kalis et al 2003). Although very few studies (n=3) in the present review determined prevalences using this type of tests, previous information from Brazilian studies suggests that the intradermal tuberculin tests can interfere in the reliability of ELISA (Lilenbaun et al 2007(Lilenbaun et al , 2009Varges et al 2009) and that serological testing for PTB should be avoided for 90 days after PPD inoculation ). Studies on paratuberculosis in Latin America and the Caribbean rarely reported tuberculosis status or previous tuberculin tests before paratuberculosis testing, which could suggest that results could be higher than reported.…”
Section: Discussionmentioning
confidence: 77%
“…This results in infected animals being reported as ELISA negative to MAP despite shedding MAP into the environment (Milner et al, 1987). False-positive humoral results can also arise due to bTB-infected animals, and bTB testing in herds before MAP testing without sufficient time elapsing between tests (i.e., 90 d; Lilenbaum et al, 2007;Varges et al, 2009). Environmental mycobacteria (closely related to, but excluding MAP) could also potentially result in false-positive ELISA results in the present study (Osterstock et al, 2007).…”
Section: Estimated Variance Components For Map In Comparison To Previmentioning
confidence: 75%